(untitled) (UUM Journal of Legal Studies, 2020)
In recent times, cyberspace is being widely used so that everyone has a digital account. It naturally entails its own legal issues. Undoubtedly, one of the main issues is that what fate awaits the account and its content upon the account holder’s death? This issue has been neglected not only by the primary creators of digital accounts but also by many legal systems in the world, including Iran. To answer this question, we first need to distinguish between the account and the information contained therein. The account belongs to the company that creates it and allows the user to use it only. Hence, following the death of the account holder, the account will be lost but the information will remain because it was created by him/her and thus belongs to him/her. However, does this mean that the information will be inherited by the user’s heirs after his/her death? Can the user exercise his/her right to transfer account content to a devisee through a testament? Comparing digital information with corporeal property, some commentators believe that the property will be inherited like corporeal property. This is a wrong deduction because the corporeal property can disclose the privacy of the owner and third parties less than the one in cyberspace. This paper aims to show what happens to a digital account after its user passes away and examine the subject using the content analysis method in various legal systems in the world, especially in Iran as a case study. The required information is collected from law books, articles, doctrines, case laws, and relevant laws and regulations of different countries. To protect the privacy interests of the deceased and others, it is concluded that the financially valuable information published by the account holder before his/her death can be transferred to successors. As a rule, the information that may violate privacy by divulging should be removed. However, given that this information may be a valuable source in the future to know about the present, legislators are suggested to make digital information, which may no longer lead to the invasion of the decedent’s privacy, available to the public after a long time.